On relation between radar super-refraction echoes and height of ducting layers along west coast of India (MAUSAM, 1990)
The paper presents a study of abnormal propagation of microwaves observed along the west coast of India and across Arabian Sea using a S-band radar 1ocated at Bombay. Very distant echo of Arabian Peninsula has been seen on PPI scope. The variation in the abnormal propagation has been studied ID relation to meteorological conditions using radios9nde data of RS/R Unit, Bombay. It is seen that whenever elevate Conducts are present, super-refraction echoes are also present on .PPI scope. The Increase In ground echoes is seen to be directly related to the decrease in the height of these ducting layers.